Positive electrode active material of lithium-sulfur battery as well as preparation method and application of positive electrode active material

By using porous carbon and Co9S8 composite materials as positive electrode active materials in lithium-sulfur batteries, the problem of shuttle effect is solved, the cycle performance and rate performance of the battery are improved, and the battery life is extended.

CN119833617APending Publication Date: 2025-04-15ZHONGTIAN ENERGY STORAGE TECH +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510060236.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-14
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The shuttle effect of lithium-sulfur batteries leads to a decrease in the utilization rate of sulfur positive electrode, and the dissolution of polysulfides leads to a decrease in battery capacity and Coulomb efficiency, which leads to battery failure.

Method used

Porous carbon and Co9S8 composite materials are used as the positive electrode active material. Co9S8 is supported on the porous carbon surface and pores, inhibiting polysulfide diffusion through chemical interactions, and the porous carbon structure formed by high-temperature sintering increases the sulfur loading and catalytic activity, reducing volume changes during the cycle.

Benefits of technology

It effectively inhibits the diffusion of polysulfides, improves the charge-to-movement mechanical efficiency, improves the cycle performance and rate performance of the battery, and extends the battery life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119833617A_ABST
    Figure CN119833617A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of lithium-sulfur batteries, and particularly provides a positive electrode active material of a lithium-sulfur battery as well as a preparation method and application of the positive electrode active material. The positive electrode active material of the lithium-sulfur battery comprises porous carbon and Co9S8, the Co9S8 is loaded and distributed on the surface and in pores of the porous carbon, the porous carbon has an effective physical limiting effect on polysulfide, and the Co9S8 and the polysulfide have a strong chemical effect, so that anchoring of the polysulfide can be remarkably improved, and the performance of the lithium-sulfur battery is improved. Co9S8 has high catalytic activity and can promote the conversion of polysulfide, and the positive electrode active material combines the chemical effects of a porous carbon structure and Co9S8, effectively improves the shuttle effect of a lithium-sulfur battery, and improves the cycle performance and rate capability of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium-sulfur batteries, and in particular to a positive electrode active material of a lithium-sulfur battery and a preparation method and application thereof. Background Art

[0002] The conversion and storage of electrical energy is becoming one of the focal points of the future low-carbon society. Lithium-ion batteries can no longer meet the growing demand for high-performance energy systems, and new battery systems need to be explored to show higher energy density and longer cycle life. The theoretical specific capacity of lithium-sulfur batteries can reach 1675 mAh / g. Therefore, lithium-sulfur batteries have broad prospects in achieving a quantum leap in energy storage and solving current challenges. However, the shuttle effect of lithium-sulfur batteries causes a sharp drop in the utilization rate of the sulfur positive electrode, resulting in a rapid decrease in capacity, a gradual decrease in Coulomb efficiency, and ultimately battery failure. One of the main reasons for the shuttle effect is that during the charge and discharge process of lithium-sulfur batteries, a variety of intermediate polysulfides are generated. These polysulfides are easily soluble in the electrolyte. Part of the polysulfides obtain electrons on the positive electrode side and are reduced to remain in the positive electrode, while the other part "shuttles" from the positive electrode to the negative electrode due to the difference in concentration gradient. At the negative electrode, these polysulfides react with lithium metal to generate solid insulating materials, which are deposited on the surface of lithium metal, resulting in corrosion and passivation of the metal lithium negative electrode.

[0003] In the past few years, a lot of efforts have been invested to alleviate the shuttling problem, including cathode material improvements, separator improvements, and electrolyte customization. The design and engineering of sulfur host materials to confine active sulfur intermediates has been shown to be a successful approach to improve the capacity and cycling stability of sulfur electrodes. Summary of the invention

[0004] The present invention aims to solve one of the technical problems in the prior art to at least a certain extent. To this end, one object of the present invention is to provide a positive electrode active material for a lithium-sulfur battery and a preparation method and application thereof.

[0005] In a first aspect of the present invention, a positive electrode active material for a lithium-sulfur battery is provided. The positive electrode active material comprises: porous carbon and Co9S8, wherein the Co9S8 is loaded and distributed on the surface and in the pores of the porous carbon.

[0006] According to the positive electrode active material of the lithium-sulfur battery of the present invention, reference Figure 1, including porous carbon and Co9S8. First, porous carbon has a large pore size and specific surface area, so it can effectively load sulfur substances (Co9S8) and lock sulfur substances in the porous structure, so as to achieve a higher sulfur loading, thereby reducing the volume change during the cycle and improving the electrical performance of the battery. Moreover, the pore wall of porous carbon can form a physical barrier, which can make the charge transfer reaction of sulfur occur in the pore, inhibit the diffusion of polysulfides, and reduce the occurrence of the shuttle effect. Co9S8 load is distributed on the surface and pores of porous carbon. There is a strong chemical signal between Co9S8 and polysulfides, and chemical interactions can occur, which can significantly improve the anchoring of polysulfides and effectively hinder the mobility and diffusion of polysulfides in the electrolyte. At the same time, Co9S8 has a high catalytic activity, which can promote the conversion of polysulfides, thereby improving the charge transfer kinetics efficiency. Co9S8 also has a high theoretical capacity, which can improve the rate performance of the battery. Therefore, the positive electrode active material prepared by composite porous carbon and Co9S8 can fully combine the porous carbon structure and the chemical action of Co9S8, effectively improve the shuttle effect of lithium-sulfur batteries, and improve the cycle performance and rate performance of the battery.

[0007] According to the positive electrode active material of the lithium-sulfur battery of the present invention, the pore size of the porous carbon is 2nm~7nm. By controlling the pore size of the porous carbon within the above range, a high loading amount of the catalyst Co9S8 can be achieved.

[0008] According to the positive electrode active material of the lithium-sulfur battery of the present invention, the specific surface area of ​​the porous carbon is 20 m 2 / g~40.082m 2 The specific surface area of ​​the porous carbon is within the above range, which can be beneficial to improving the contact area between the catalyst and the polysulfide and accelerating the reaction kinetics.

[0009] According to the positive electrode active material of the lithium-sulfur battery of the present invention, the mass ratio of the porous carbon to Co9S8 is 100: (100-400). When the mass ratio of the porous carbon to Co9S8 is within the above range, the best effect of the synergistic effect of the two can be achieved.

[0010] In a second aspect of the present invention, the present invention provides a method for preparing the positive electrode active material of the above-mentioned lithium-sulfur battery, the method comprising: The super absorbent resin is mixed with the cobalt sulfate solution and allowed to stand for adsorption, and then freeze-dried and sintered at high temperature.

[0011] According to the method for preparing the positive electrode active material of the lithium-sulfur battery of the present invention, a super absorbent resin is used as a carbon source as a precursor. The super absorbent resin can adsorb inorganic salt solutions and has good pore-forming ability. A porous carbon material with a large specific surface area can be prepared, which can effectively adsorb cobalt sulfate. Then the above-mentioned adsorption mixed solution is freeze-dried, the solvent is removed, and then sintered at high temperature to obtain a sulfide / porous carbon (Co9S8 / C) positive electrode active material. Therefore, the method can be used to prepare a lithium-sulfur battery positive electrode active material that can effectively inhibit the shuttle effect.

[0012] According to the method for preparing the positive active material of the lithium-sulfur battery of the present invention, the concentration of the cobalt sulfate solution is 0.5mol / L~3mol / L. For example, the concentration is 0.5mol / L, 1mol / L, 1.5mol / L, 2mol / L, 2.5mol / L, 3mol / L, etc., or the range between any two values ​​of the above. The use of the cobalt sulfate solution of the above concentration is convenient for the super absorbent resin to adsorb it, and a certain amount of cobalt sulfate can be adsorbed, which is beneficial to increase the content of sulfide in the positive active material, thereby improving the electrical performance of the battery. Further, the cobalt sulfate is dissolved in deionized water to form a cobalt sulfate solution.

[0013] According to the method for preparing the positive active material of the lithium-sulfur battery of the present invention, the super absorbent resin includes a cellulose super absorbent resin, a synthetic resin super absorbent resin or an organic-inorganic composite super absorbent resin. The above super absorbent resin can have a good adsorption effect on cobalt sulfate, so that the formed carbon material can load more sulfides. At the same time, the above super absorbent resin can form a porous carbon material, and the formed carbon material has a better physical confinement effect on polysulfides.

[0014] According to the method for preparing the positive active material of lithium-sulfur battery of the present invention, the time of static adsorption is 2 to 4 days. For example, 2 days, 3 days, 4 days, etc., or the range between any two values ​​of the above. Controlling the time of static adsorption within the above range is conducive to the adsorption of cobalt sulfate by the resin. Further, the temperature of the static adsorption is 20°C to 30°C.

[0015] According to the method for preparing the positive active material of the lithium-sulfur battery of the present invention, the freeze-drying temperature is -25°C to -15°C. Further, the solution is frozen with liquid nitrogen and then freeze-dried at -25°C to -15°C to remove water molecules.

[0016] According to the method for preparing the positive active material of the lithium-sulfur battery of the present invention, the temperature of the high-temperature sintering is 800°C to 1100°C, and the time is 3h to 5h. Further, the high-temperature sintering is carried out in a nitrogen atmosphere, for example, the sintering temperature is 800°C, 900°C, 1000°C, 1100°C, etc., or the range between any two of the above values, and the sintering time is 3h, 4h, 5h, etc., or the range between any two of the above values. By controlling the sintering temperature and time within the above range, the pore size and specific surface area of ​​the formed carbon material can be controlled, thereby improving the physical limiting effect of the carbon material on polysulfides and the loading effect on sulfides.

[0017] In a third aspect of the present invention, the present invention provides a positive electrode sheet, which includes the positive electrode active material or the positive electrode active material prepared by the above method. Therefore, the positive electrode sheet has good stability, and the battery prepared by using the positive electrode sheet has a lower shuttle effect.

[0018] In some embodiments of the present invention, the positive electrode sheet further includes a binder and a conductive agent.

[0019] As examples, the binder includes polyvinylidene fluoride, carboxylated polyvinylidene fluoride, modified SBR rubber, modified fluorinated rubber, modified polyurethane, and the like.

[0020] As examples, the conductive agent includes carbon black, carbon nanotubes, graphene, and the like.

[0021] In some embodiments of the present invention, the preparation process of the positive electrode plate includes: stirring and mixing the positive electrode active material, conductive agent, binder, and solvent to obtain a mixed slurry, and then evenly coating the mixed slurry on an aluminum foil and vacuum drying it to obtain a positive electrode plate.

[0022] In a fourth aspect of the present invention, the present invention provides a lithium-sulfur battery, which includes the above-mentioned positive electrode plate, so that the lithium-sulfur battery has long cycle capacity and stability.

[0023] In some embodiments of the present invention, the lithium-sulfur battery further comprises a negative electrode plate and a battery separator. Further, the negative electrode plate can be a metal lithium plate, and the battery separator can be a polypropylene porous film. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0025] Figure 1This is an electron microscope image of the positive electrode active material of Example 6 of the present invention. DETAILED DESCRIPTION

[0026] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. The present invention is described below with reference to specific embodiments. It should be noted that these embodiments are merely illustrative and do not limit the present invention in any way.

[0027] Example 1 The preparation process of the positive electrode active material of this embodiment is as follows: (1) Weigh cobalt sulfate and dissolve it in 100 ml of deionized water. Heat and stir for half an hour until the solid is fully dissolved. The concentration of the prepared cobalt sulfate solution is 1 mol / L. Then add super absorbent resin balls (Shouke New Materials 580H) and let it stand for 3 days for adsorption. After sufficient adsorption, take it out, freeze it with liquid nitrogen, and then freeze-dry it at -20°C.

[0028] (2) The freeze-dried solid was placed in a crucible, transferred to a tube furnace, and sintered at 800°C for 4 h under argon. The sintered sample was washed with hydrochloric acid for 2 h and dried at a constant temperature of 60°C to obtain the Co9S8 / C positive electrode active material.

[0029] The pore size of the prepared porous carbon positive electrode active material is 4.126nm and the specific surface area is 40.082m 2 / g, the mass ratio of porous carbon to Co9S8 is 100:157.

[0030] Example 2 The difference between the preparation process of the positive electrode active material of this embodiment and that of embodiment 1 is as follows: (2) The freeze-dried solid was placed in a crucible, transferred to a tube furnace, and sintered at 900°C for 4 h under argon. The sintered sample was washed with hydrochloric acid for 2 h and dried at a constant temperature of 60°C to obtain the Co9S8 / C positive electrode active material.

[0031] The pore size of the prepared positive electrode active material porous carbon is 4.833nm and the specific surface area is 39.476m 2 / g, and the mass ratio of porous carbon to Co9S8 is 100:154.

[0032] Example 3 The difference between the preparation process of the positive electrode active material of this embodiment and that of embodiment 1 is as follows: (2) The freeze-dried solid was placed in a crucible, transferred to a tube furnace, and sintered at 1000°C for 4 h under argon. The sintered sample was washed with hydrochloric acid for 2 h and dried at a constant temperature of 60°C to obtain the Co9S8 / C positive electrode active material.

[0033] The pore size of the prepared positive electrode active material porous carbon is 5.698nm and the specific surface area is 35.159m 2 / g, the mass ratio of porous carbon to Co9S8 is 100:149.

[0034] Example 4 The difference between the preparation process of the positive electrode active material of this embodiment and that of embodiment 1 is as follows: (2) The freeze-dried solid was placed in a crucible, transferred to a tube furnace, and sintered at 1100°C for 4 h under argon. The sintered sample was washed with hydrochloric acid for 2 h and dried at a constant temperature of 60°C to obtain the Co9S8 / C positive electrode active material.

[0035] The pore size of the prepared positive electrode active material porous carbon is 6.348nm and the specific surface area is 33.324m 2 / g, and the mass ratio of porous carbon to Co9S8 is 100:140.

[0036] Example 5 The difference between the preparation process of the positive electrode active material of this embodiment and that of embodiment 1 is as follows: (1) Weigh cobalt sulfate and dissolve it in 100 ml of deionized water. Heat and stir for half an hour until the solid is fully dissolved. The concentration of the prepared cobalt sulfate solution is 3 mol / L. Then add super absorbent resin balls and let it stand for 3 days for adsorption. After sufficient adsorption, take it out, freeze it with liquid nitrogen, and then freeze-dry it at -20°C.

[0037] The pore size of the prepared positive electrode active material porous carbon is 2.968nm and the specific surface area is 20.652m 2 / g, the mass ratio of porous carbon to Co9S8 is 100:106.

[0038] Example 6 The difference between the preparation process of the positive electrode active material of this embodiment and that of embodiment 1 is as follows: (1) Weigh cobalt sulfate and dissolve it in 100 ml of deionized water. Heat and stir for half an hour until the solid is fully dissolved. The concentration of the prepared cobalt sulfate solution is 2 mol / L. Then add super absorbent resin balls and let it stand for 3 days for adsorption. After sufficient adsorption, take it out, freeze it with liquid nitrogen, and then freeze-dry it at -20°C.

[0039] The pore size of the prepared positive electrode active material porous carbon is 3.477nm and the specific surface area is 29.436m 2 / g, and the mass ratio of porous carbon to Co9S8 is 100:390.

[0040] Example 7 The difference between the preparation process of the positive electrode active material of this embodiment and that of embodiment 1 is as follows: (1) Weigh cobalt sulfate and dissolve it in 100 ml of deionized water. Heat and stir for half an hour until the solid is fully dissolved. The concentration of the prepared cobalt sulfate solution is 0.5 mol / L. Then add super absorbent resin balls and let it stand for 3 days for adsorption. After sufficient adsorption, take it out, freeze it with liquid nitrogen, and then freeze-dry it at -20°C.

[0041] The pore size of the prepared positive electrode active material porous carbon is 4.986nm and the specific surface area is 33.573m 2 / g, and the mass ratio of porous carbon to Co9S8 is 100:142.

[0042] Comparative Example 1 (1) Dissolve the super absorbent resin beads in 100 ml of deionized water, let stand for 3 days for adsorption, take them out after sufficient adsorption, freeze them with liquid nitrogen, and then freeze-dry them at -20°C.

[0043] (2) The freeze-dried solid was placed in a calcined solution, transferred to a tubular furnace, and sintered at 800°C for 4 h under hydrogen gas. The sintered sample was washed with hydrochloric acid for 2 h and dried at a constant temperature of 60°C to obtain a porous carbon material.

[0044] The pore size of the prepared porous carbon material is 2.846 nm and the specific surface area is 12.59 m 2 / g.

[0045] The performance of the positive electrode active materials of the above embodiments and comparative examples was tested, and the specific testing method is as follows: (1) The active material sulfur, conductive carbon and PVDF are mixed in a ratio of 7:2:1 to form a positive electrode. The cathode is made of Li metal and the anode is assembled into a 2032-type button battery in the order of anode shell, spring, gasket, lithium sheet, separator, cathode material and cathode shell.

[0046] (2) Using the Xinwei battery testing system, a constant current charge and discharge experiment was performed on the lithium-sulfur battery. The long cycle current is 1C, and the rate charge and discharge current is 1-5C. At a constant temperature of 30°C, the test The voltage range is between 1.7V and 2.7V.

[0047] The performance test results of the positive electrode active materials of the above examples and comparative examples are shown in Table 1.

[0048] Table 1

[0049] In order to determine the optimal carbonization temperature, a series of experiments were carried out, and sulfides can be synthesized at 800-1100°C. Performance-oriented, the carbonization temperature of 900°C is optimal. At this temperature, the concentration of the CoS04 solution was adjusted to take into account the effect of the sulfide concentration on the microstructure of the product. In Comparative Example 1, the carbon is accumulated in the form of nanoparticles accumulated into large agglomerates, which may be due to the collapse of its pore structure due to high-temperature sintering. However, with the incorporation of CoS04, the morphology of the product changed significantly as the concentration of the solution increased, and the pore structure became more and more prominent. When the concentration increased to 3M, the presence of excessive Co9S8 caused a large number of large particles to aggregate, which had a negative impact on the electrochemical reaction. Example 6 In a CoSO4 solution with a concentration of 2M, the morphology showed the best regularity ( Figure 1 As shown), the carbon exhibits a clear macroporous structure, and Co9S8 is loaded on the surface of the carbon material, which is beneficial to the loading of sulfur and the conversion between polysulfides.

[0050] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A positive electrode active material for a lithium-sulfur battery, characterized in that: include: Porous carbon and Co9S8, Co9S8 loading is distributed on the surface and pores of the porous carbon.

2. The positive electrode active material according to claim 1, characterized in that: The pore size of the porous carbon is 2nm~7nm; And / or, the specific surface area of ​​the porous carbon is 20m 2 / g~40.082m 2 / g.

3. The positive electrode active material according to claim 1 or 2, characterized in that: The mass ratio of the porous carbon to Co9S8 is 100:(100~400).

4. A method for preparing a positive electrode active material for a lithium-sulfur battery according to any one of claims 1 to 3, characterized in that: include: The super absorbent resin is mixed with the cobalt sulfate solution and allowed to stand for adsorption, and then freeze-dried and sintered at high temperature.

5. The method according to claim 4, characterized in that: The concentration of the cobalt sulfate solution is 0.5 mol / L to 3 mol / L.

6. The method according to claim 4 or 5, characterized in that: The super absorbent resin includes a cellulose super absorbent resin, a synthetic resin super absorbent resin or an organic-inorganic composite super absorbent resin.

7. The method according to claim 4 or 5, characterized in that: The static adsorption time is 2 to 4 days; And / or, the temperature of the static adsorption is 20°C to 30°C; And / or, the freeze-drying temperature is -25°C to -15°C.

8. The method according to claim 4 or 5, characterized in that: The high temperature sintering temperature is 800° C. to 1100° C., and the time is 3 h to 5 h.

9. A positive electrode sheet, characterized in that: The invention comprises the positive electrode active material according to any one of claims 1 to 3 or the positive electrode active material prepared by the method according to any one of claims 4 to 8.

10. A lithium-sulfur battery, characterized in that: Including the positive electrode sheet as described in claim 9.